Accidental & Homicidal Limb Injuries Reporting at Bone Care & Trauma Center - Salman Ahmed Farsi Kazi, Parvez Rais Khan, Mustafa Parvez Khan (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2014)
Objective: The present study was conducted to evaluate causes, types, patterns and medico legal aspects of limb injuries at Bone Care and Trauma Center Hyderabad. Study design: Retrospective, observational study Place and Duration: Bone Care and Trauma Center Hyderabad from Jan to Dec 2013. Subjects and Methods: Patient’s files of January to December 2013 were evaluated retrospectively. 5600 files of patients were checked, of which 1087 were included in study protocol. The required data was collected on pre designed proforma. The variables were typed on SPSS version 21.0 for analysis. Continuous and categorical variables were analyzed using students t-test and chi-square test. Microsoft excel was also used for graphing purpose. P-value = 0.05 was defined as significant. Results: Of total 1087, 901 (82.8%) were male and 186 (17.1%) were female. (p=0.0001). Mean±SD age was noted as 39±11.5 years. Road traffic accidents were noted in 549 (50.5%), remaining cases belonged to social quarrels, assaults, fire arm injuries, falls and sport injuries. Of 1087, 1014 (93.2%) were non medico legal and 73 (6.7%) cases were medico legal, of which 41 were accidental, 23 were homicidal and 9 were of suicidal nature. Conclusion: Most common cause of limb injuries was road traffic accident, and commonly by motorcycle.